Surgeons' recommendation is the factor in determining the breast cancer surgery procedures: An experience from rural hospital in Thailand - Ajaree Sattaratnamai (2019)
© 2018 Asian Pacific Organization for Cancer Prevention. Introduction: The majority of breast cancer patients in rural hospital in developing countries still warrant for total mastectomy. Surgeon advice regard surgical procedure is one of the most important factors in decision making. Our study aims to compare the rate of breast-conserving surgery (BCS), mastectomy (MT) and mastectomy with immediate breast reconstruction (MTIBR) between the surgeons who offer only MT (group A) and who offer BCS MT and MTIBR (group B). Method: A retrospective cohort study was conducted at Ratchaburi hospital, Thailand from January 2010 to April 2014. We categorized patients into 2 groups (group A and B). Univariated analysis was selected to determine the factors that associated with the breast surgery procedures. Results: From January 2010 to April 2014, we recruited 310 breast cancer patients, 221 patients (71.2%) were treated by surgeons in group A, 89 patients (28.7%) by surgeons in group B. The choice of breast surgery is significantly different between 2 groups (P < 0.001). In group A, 213 (96.3%) patient had MT and only 3 (1.3%) BCS and 5 (2.2%) MTIBR. Whilst in group B, 58 (65.1%) patient had MT and 11 (12.3%) BCS and 20(22.4%) MTIBR. Choice of breast surgery in patients with stage 1,2,3 are significantly different between 2 groups (P=0.004, < 0.001, 0.025 respectively). Age is the only factor that significantly affects the choice of surgery in the group B but not in group A. Conclusion: Surgeon's competency and comprehensive preoperative consultation by offering BCS, MT and MTIBR can affect the choice of surgical procedure for breast cancer patient.